2017
DOI: 10.1111/ajd.12588
|View full text |Cite
|
Sign up to set email alerts
|

Mucinous Naevus: A case of suboptimal response to laser treatment

Abstract: Primary amyloid deposition on the hair-bearing regions of the scalp has been reported with nodular amyloidosis in association with Sjogren's syndrome. 1 To the best of our knowledge, lichen amyloidosis has not previously been reported to affect the hair bearing scalp.Lichen amyloidosis is characterised by the accumulation of amyloid derived from keratin in the papillary dermis. Associations reported with lichen amyloidosis include multiple endocrine neoplasia type 2 (Sipple syndrome), which can be screened fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…As in the latter, hypertrophic scarring may be a complication of laser therapy, surgical excision alone is more acceptable in order to achieve good cosmetic results. 46…”
Section: Management and Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…As in the latter, hypertrophic scarring may be a complication of laser therapy, surgical excision alone is more acceptable in order to achieve good cosmetic results. 46…”
Section: Management and Prognosismentioning
confidence: 99%
“…Combined mucinous naevus, associating epidermal naevus with dermal mucin, has been considered suitable for laser ablation with carbon dioxide laser, while pure mucinous dermal naevus is not. As in the latter, hypertrophic scarring may be a complication of laser therapy, surgical excision alone is more acceptable in order to achieve good cosmetic results …”
Section: Mucinous Naevusmentioning
confidence: 99%
“…Chi et al ( 6 ) proposed that carbon dioxide laser vaporization may be a treatment option for mucinous naevus of the combined epidermal-CTNP type with multiple exophytic and verrucous lesions, but not for the CTNP type. However, Mulcahy et al ( 7 ) reported a case of combined-CTNP type, in which carbon dioxide laser resurfacing resulted in hypertrophic scarring despite being performed by an experienced laser dermatologist. Thus, the outcome of such treatment is unpredictable.…”
mentioning
confidence: 99%